CFD Modeling and Computation of Convective Heat Coefficient Transfer of Automotive Disc Brake Rotors - Belhocine, Ali; Wan-Omar, Wan Zaidi (Revista Científica, 2017)
Braking system is one of the important control systems of an automotive. For many years, the disc brakes have been used in automobiles for safe retardation of the vehicles. During braking enormous amount of heat will be generated and for effective braking sufficient heat dissipation is essential. The thermal performance of disc brake depends upon the characteristics of the airflow around the brake rotor and hence the aerodynamics is an important in the region of brake components. A CFD analysis is carried out on the braking system as a case study to make out the behaviour of airflow distribution around the disc brake components using ANSYS CFX software. We are interested in the determination of the heat transfer coefficient (HTC) on each surface of a ventilated disc rotor varying with time in a transient state using CFD analysis, and then imported the surface film condition data into a corresponding FEM model for disc temperature analysis.